Valorisation of underutilized grass fibre (stem) as a potential material for paper production - Lee, Chuan Li; Chin, Kit Ling; H’ng, Paik San; Hafizuddin, Mohd Sahfani; Khoo, Pui San (MDPI AG, 2022)
An integrated and feasible approach was proposed using the underutilized grass fibre (stem) derived from Napier grass and sugarcane for paper production in this study. To enhance paper strength, pre-hydrolysis and beating techniques have been used to improve the chemical pulps and mechanical pulping process, respectively. Napier grass and sugarcane are promising non-wood sources for pulp production, owing to their high cellulose and low lignin and extractive content. With the additional mild alkaline pre-treatment to the mechanical pulping process, t he lig nin content was greatly reduced. The results reveal that the mechanical pulping with alkaline pre- treatment may indeed potentially replace the most prevalent pulping process (chemical pulping). As evidenced by the paper strength properties, mechanical pulping is far more suitable for grass-type biomass, particularly Napier grass, which had a folding endurance capability five times greater than chemical pulping. Furthermore, the remaining high hemicellulose content from mechanical pulping contributed to a high pulp yield, while also facilitating the fibrillation on the sugarcane’s laboratory paper handsheet. The findings also demonstrated that the additional beating process from chemical pulping causes the fibres to be drawn toward each other, resulting in a more robust fibre network that contributes to good paper strength. Consequently, this work sheds new light on the development of advanced paper derived from grass fibre.